Memory Foam Pillow as an Intervention in Obstructive Sleep Apnea Syndrome: A Preliminary Randomized Study - Stavrou, Vasileios T.; Koutedakis, Yiannis; Astara, Kyriaki; Vavougios, George D.; Papayianni, Eirini; Stavrou, Ilias T.; Bardaka, Fotini; Pastaka, Chaido; Gourgoulianis, Konstantinos I. (Frontiers in Medicine, 2022)
Pillow use affects sleep quality by directly maintaining the cervicospinal natural curvature and assisting airway patency. The aim of this study was to investigate the effect of different pillows [own pillow (OP), foam-memory pillow (MFP), generic laboratory pillow (LP)] on selected polysomnography (PSG)V-derived parameters in patients with OSAS. Thirty-two consecutive OSAS patients were randomly allocated into two groups [Group A: 3 hours with LP and 3 hours with OP (Age: 53.8±12.5 yrs, BMI: 32.1±4.6 kg/m2); Group B: 3 hours with LP and 3 hours with MFP (Age: 52.0±6.3 yrs, BMI: 30.6±2.2 kg/m2)]. Pillow placement was randomized. Statistically significant differences were detected between polysomnography (PSG) parameters such desaturation (p<0.05) between pillows and heart rate between groups (p<0.05), and between pillow types (p<0.05). A In Group B with MFP, a decrease of 47.0±15.9 % was observed in snoring events (p<0.05) and 10.6±6.7 % in their duration (p<0.05) compared to LP. Group A with OP recorded a decrease of 29.1±32.1 % in snoring events and 32.5±33.1 % in duration, but these values were not statistically significant (p>0.05), compared to LP. These findings indicate that pillow type and usage, often uncontrolled for in OSAS studies, impact several PSG parameters and are related to a snoring subtype of the syndrome. Secondly, they indicate that a focus on the treatment of the snoring OSAS subtype warrants further, dedicated investigation.